2013
DOI: 10.1245/s10434-013-3430-7
|View full text |Cite
|
Sign up to set email alerts
|

EpCAM-Targeted Therapy for Human Hepatocellular Carcinoma

Abstract: Our preclinical investigation suggests that EpCAM-targeted therapy may offer a promising and novel approach for the treatment of HCC with a poorer prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…Previous studies reported that VB4-845, an immunotox in targeting EpCAM, showed potent cytotoxicity and was significantly effective in combination with 5-FU in hepatocellular carcinoma cells [20]. Treatment with an anti-EpCAM monoclonal antibody (MAb17-1A) combined with alpha-interferon; 5-FU and granulocyte-macrophage colony-stimulating factor could improve the therapeutic effect in patients with metastatic colorectal carcinoma [21].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that VB4-845, an immunotox in targeting EpCAM, showed potent cytotoxicity and was significantly effective in combination with 5-FU in hepatocellular carcinoma cells [20]. Treatment with an anti-EpCAM monoclonal antibody (MAb17-1A) combined with alpha-interferon; 5-FU and granulocyte-macrophage colony-stimulating factor could improve the therapeutic effect in patients with metastatic colorectal carcinoma [21].…”
Section: Discussionmentioning
confidence: 99%
“…Another approach for eliminating CSCs has been suggested to be monoclonal antibodies targeting CSC-speciic antigens [46], such as CD13, EpCAM, and CD133 antibodies, against hepatic CSCs [47][48][49]. However, these markers express in not only CSCs but also normal liver cells and tissue SCs.…”
Section: Therapy For Hccmentioning
confidence: 99%
“…Other targets in HCC include: glypican-3 (GC33), c-Met (onartuzumab), epidermal growth factor receptor (cetuximab), insulin-like growth factor-1 receptor (cixutumumab), insulin-like growth factor I and II (MEDI-573), platelet-derived growth factor receptor A (MEDI-575), activin receptor-like kinase 1 (PF-03446962), endoglin (TRC105), and TROP-2 (sacituzumab) [69,70,71,72,73,74,75]. Additional targets like EpCAM and CD133 are being evaluated in preclinical studies as potential markers for HCC [45,76,77,78]. As HCC is better understood, the list of potential targets will continue to grow.…”
Section: Anti-gpc3 Recombinant Immunotoxinsmentioning
confidence: 99%
“…Immunotoxins have been used to treat intracranial tumors in rodent models by targeting the EGF receptor expressed in glioblastomas [42]. Similarly, anti-c-Met and anti-epithelial cell adhesion molecule (EpCAM) have been evaluated for their ability to target gastric cancer and a wide range of solid tumors including breast, colon, and liver cancers, respectively [43,44,45]. Instead of substituting the antibody portion to make new immunotoxins, it is also possible to substitute the toxin fragment.…”
Section: Introductionmentioning
confidence: 99%